KARAKTERISASI RESERVOIR RINDU-5 DAN RINDU-4 DI AREA-11,LAPANGAN DURI, CEKUNGAN SUMATRA TENGAH - Arifin, Slamet
Area-11 which has an area of about 6 km2 is part of the northern part of Duri field has been developed since 2003. Area-11 that was developed by steam injection system implementation still leaves some problems that result in less optimal depletion of oil in this area. There are two unresolved issues are: the distribution of Rindu-5 and Rindu-4 facies could not be identified in detail and less efficiency of steam injection that was injected into the reservoir. Distribution of Rindu-5 and Rindu-4 facies is very important to understand because those facies will result reservoir heterogenity that impact to reservoir response to steam injection. The method used in this study is the identification of rock facies of core data to obtain a succession of facies models are then used for chronostratigraphic correlation to obtain time-frame picture of the deposition, lateral distribution, and reservoir geometry. Reservoir quality mapping is also conducted to obtain a picture of the quality of reservoir heterogeneity as a reflection of the diversity of characters in the body of the reservoir facies associations. The results showed that the Rindu-5 reservoir is a succession of fluvial channel facies toward the tidal sand ridge facies. The lower part of this facies succession is limited by a sequence boundary due to the process of regression to the base level, then form incised valley systems which is filled by fluvial channel facies associations and accretionary bank. The next process is the phase that produces transgression facies associations and tidal mud flats and tidal sand ridge. Reservoir quality Rindu-5 and Rindu-4 are varied and controlled by the permeability of each facies. Variations in reservoir quality is a factor affecting the distribution of steam in the reservoir. The results of this reservoir characterization for subsequent use as a guide in evaluating the development of area-11 at this time and further areas of development strategies. Evaluation of the development area focused on patterns that are located in regions of low permeability, ie the pattern size reduction project plan (smaller pattern) that will accelerate the steam breaktrough time in producer wells, while the area development strategy is focused on developing new region in the northwestern part of the pattern by applying a small (4-5 acres). Smaller pattern project that that has been done in the area-11 has been done only on evaluation of data on production and steam injection and not involve aspects of reservoir characterization because there has been no detailed studies on the characterization of the reservoir at the time. With the results of reservoir characterization, field development activities will be more focused and achieve optimal results.